Philippine development issues : an inquiry - Tendero, Avelino P.; Reyes, Dolores A.; Manas, Maria Socorro F. (Metro Manila, Philippines : National Book Store, 1984)
The Balikbayan Program of the Ministry of Tourism enticed a brother-sister duo to visit the Philippines after an absence of some thirty years. Their sentimental journey sought to recapture some of their lost youth.
Unit I. Social institution and social interaction -- Unit II. The problems of the community -- Unit III. Population education.
Includes bibliographical references.
Keywords: SOCIAL CONDITION